2012
DOI: 10.1007/s00128-012-0543-9
|View full text |Cite
|
Sign up to set email alerts
|

Metals in Fish along the Southeast Coast of India

Abstract: Metal concentrations (cadmium, chromium, iron, lead, copper, manganese, zinc and mercury) in the muscle of five fish species (Epinephelus chlorostigma, Lutjanus russelli, Terapon jarbua, Cynoglossus arel and Lagocephalus lunaris) from the six fish landing centres along southeast coast of India were measured. In Cuddalore and Mudasalodai, the level of toxic metals cadmium, chromium and manganese were well above the permissible limits. Concentrations of cadmium, chromium, manganese and mercury in C. arel were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Other characteristics are also determinant for biota metalscontent, as pointed out by Velusamy et al in their Mumbay Bay (India) findings, with higher trace metal accumulation in demersal fish followed by neritic and pelagic fish (88). Additionally, aquatic ecosystem environmental conditions like the level of contamination, increase metal concentrations due to fish susceptibility to toxic substances present in water, as stated by Thiyagarajan et al, on their studies in different zones on the southwest coast of India related to high populations and industrial effluents as the main metal contamination sources in coastal waters (55).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Other characteristics are also determinant for biota metalscontent, as pointed out by Velusamy et al in their Mumbay Bay (India) findings, with higher trace metal accumulation in demersal fish followed by neritic and pelagic fish (88). Additionally, aquatic ecosystem environmental conditions like the level of contamination, increase metal concentrations due to fish susceptibility to toxic substances present in water, as stated by Thiyagarajan et al, on their studies in different zones on the southwest coast of India related to high populations and industrial effluents as the main metal contamination sources in coastal waters (55).…”
Section: Discussionmentioning
confidence: 91%
“…Levels of Hg, Cd, Pb and As in water bodies determine significantly the content of these elements in fish tissues (55,93), therefore it's not enough with only know characteristics such as species, age and size of the fish, but also take into account these metal releases from natural and anthropogenic sources into marine ecosystems. Although exist reports of the metals concentration in several oceans from the world, more studies about their distribution in the water bodies are required to understand the metals behavior in marine currents, allow the development of models for measuring the relationship between emission sites and reception regions (94,95).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there has been no study of Pb levels of L. sceleratus; however, Thiyagarajan et al, (2012) reported that the levels of Pb were below the limits of L. lunaris found in the same genus with L. sceleratus. Turan et al, (2009) reported Pb levels of different fish species caught in the Iskenderun Bay between 0.06 and 0.56 (μg g-1 dw).…”
Section: Discussionmentioning
confidence: 99%
“…For the Pb level, it was determined to be below Turkish Food Codex (TFC, 2011), FAO (1983) and European Commission (EC, 2001) legal limits in all four seasons. Thiyagarajan, Dhaneesh, Kumar, Kumaresan and Balasubramanian (2012) reported Pb levels in pufferfish belonging to the species Lagocephalus lunaris was below legal limits. It is thought that this might be the result of the region, due to high levels of maritime activity and industrial waste dumping in the Mersin Bay.…”
Section: Element Composition Of L Sceleratusmentioning
confidence: 99%